2010
DOI: 10.1159/000322495
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy Status Is a Key Parameter to Stratify the Prognostic Heterogeneity of Malignant Melanoma in High-Risk Tumors >4.0 mm

Abstract: Background: The value of sentinel lymph node biopsy (SLNB) as a useful strategy to assess the risk of future metastasis in high-risk melanomas (>4.0 mm) is controversially discussed. Objectives: In a single-center retrospective study, the prognostic relevance of SLNB and other risk factors in the subgroup of melanomas >4.0 mm was investigated and compared to previously published results. Methods: Using Kaplan-Meier estimates and Cox regressions, we assessed the prognostic relevance of SLNB in our subcohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
1
11
1
Order By: Relevance
“…In this study, we also found an additional impact of ulceration in SLN-positive patients. In this study, the shortest PFS and OS were found in SLN-positive patients with ulceration of the primary melanoma, and this finding is in accordance with the results of Goeppner et al [31]. Therefore, patients with a thick ulcerated melanoma would clearly benefit from the accurate staging provided by SLNB.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we also found an additional impact of ulceration in SLN-positive patients. In this study, the shortest PFS and OS were found in SLN-positive patients with ulceration of the primary melanoma, and this finding is in accordance with the results of Goeppner et al [31]. Therefore, patients with a thick ulcerated melanoma would clearly benefit from the accurate staging provided by SLNB.…”
Section: Discussionsupporting
confidence: 92%
“…The lowest 5-year PFS and OS were found in patients with a positive SLN and a history of an ulcerated melanoma. Goeppner et al have also reported a significant influence of SLN status on PFS and OS in patients with malignant melanoma of thickness >4.00 mm [31]. In their study, PFS and OS were significantly different between patients with ulcerated and with nonulcerated tumours, whereas our study showed only a tendency for a worse prognosis in patients with ulcerated melanomas.…”
Section: Discussioncontrasting
confidence: 71%
“…This stratification may create some concerns when comparing different studies. We should point out that several authors [4][5][6][7][8][9][10][11][12] stated that sentinel lymph node status predicts DFS as well as OS in patients with thick melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Fairbairn et al achieved similar results in their study. 3 Several other authors [4][5][6][7][8][9][10][11][12] have been successful in correlating the SNB--based staging with improved DFS and OS, advocating its use in this subset of patients. The results presented by Vermeeren et al 13 suggest that the only relevant prognostic factor regarding patients with thick melanoma is SNB and this procedure can be used to stratify patients according to the risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Initially identified as an adverse prognostic parameter by Allen and Spitz in 1953 [35], subsequently validated by Balch et al [36], and later on by numerous other studies [3739], ulceration has been convincingly shown to be an independent predictor of sentinel status and overall survival even in high-risk thick melanomas >4 mm [40, 41]. Despite its inclusion in the AJCC classification already in 2001 [42], the knowledge about why, when, and for what reason ulceration occurs and how it favours tumor progression is at best theoretical.…”
Section: Clinicopathological Parameters In Malignant Melanomamentioning
confidence: 99%